Male attraction of Gymnandrosoma aurantianum (Lepidoptera: Tortricidae), from Guatemala, to its sex pheromone major component is not affected by the addition of secondary components. Issue 1 (12th December 2022) - Aranda-Arguello, R.; Rojas, J.C.; Malo, E.A.; López-Guillén, G.; Cruz-López, L.
Abstract: The macadamia nut borer, Gymnandrosoma aurantianum Lima (Lepidoptera: Tortricidae), is the main pest of Macadamia integrifolia Maiden and Betche (Proteaceae) in Central America. We identified five compounds in female sex pheromone gland extracts, ( E )-8-dodecenyl acetate, tetradecyl acetate, dodecyl acetate, ( E )-8-dodecenol, and ( Z )-8-dodecenyl acetate, in a ratio of 100:44.9:33.4:6.5:1.2, respectively, from Guatemalan populations of this insect. All compounds except tetradecyl acetate elicited electroantennography responses in two- to five-day-old males. In field tests, traps baited with single compounds did not capture males, except for the major component ( E )-8-dodecenyl acetate. Mixtures of ( E )-8-dodecenyl acetate with secondary components were active in field tests, but the number of G. aurantianum males trapped did not differ between these mixtures and ( E )-8-dodecenyl acetate alone. Doses of more than 1 mg (1.5 or 2 mg) of the major component did not significantly increase capture. The gradual loss of the amount of ( E )-8-dodecenyl acetate in rubber septa under field conditions indicates that septa should be renewed every four weeks. In conclusion, the addition of secondary components to the major component of the sex pheromone gland contents does not improve capture of G. aurantianum males. Our results demonstrate that 1 mg of ( E )-8-dodecenyl acetate could be used as an attractant for monitoring populations of this moth.